Analisis Teori Sosial Tentang Pengaruh Etika Protestan terhadap Perkembangan Kapitalisme Modern - Gomer Omega Bani; Andrian Wira Syahputra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this analysis is to explore the relationship between the Protestant ethic and the development of modern capitalism, and to analyze the influence of Protestant ethical values ​​on economic and social dynamics. In addition, this analysis aims to identify shortcomings in existing studies, including theoretical focus and broader social impacts, in order to produce a more comprehensive understanding of the interaction between the Protestant ethic, capitalism, and the social context. The method used is a literature review, which involves analyzing literature related to social theory, especially Max Weber's thoughts, as well as criticism of his approach. The results of the study indicate that although the Protestant ethic has an important role, other factors such as technological progress, social change, and political structures also contribute to shaping modern capitalism. In addition, the issue of social inequality and injustice that may arise from the application of these ethical values ​​requires more attention in future studies. Thus, this study emphasizes the need for a more holistic approach to understanding the complex interaction between the Protestant ethic, capitalism, and the broader social context.